PERILAKU SATUAN POLISI PAMONG PRAJA DALAM PELAYANAN KETERTIBANDI KABUPATEN PUNCAK JAYA PROVINSI PAPUA - WONDA, DAMISON; LENGKONG, FLORENCE; KOLONDAM, HELLY (Sam Ratulangi University, 2019)
The Purpose Of This Study Was To Explain The Behavior Of The Pamong Praja Police Unit In TheService Of Order In The Glorious Peak Distrct Data Collection Uses Interview Documentation While DataAnalysis Techniques Are Carried Out Through The Stages Of Data Colletion Editorial Data PresentationData Based On The Results Of Data Analysis Concluded That The Behavior Of In Order Service In TheHigh Peak Ditricts Of Papua Proince Observed From Two Criteria Namely Preventive And Repressive YetMaximizing Public ServiceBased On The Results Of The Study It Was Found That The Behavior Of The Civil Service UnitIn Service Had Not Been Maximized So That They Could Recommend Advice The Quality Of HumanResources Head Of Civil Service Police And Pol Pp Members Need To Be Increased Through GovernmentRegulation Number 6 Years In 2014 , Civil Service Police Unit Explaind That The Civil Service Police UnitWas Part Of The Regional Apparatus In The Enforcement Of The Regional Regulations To Carry OutPublic Order And The Peace Of The People At The Level So That There Was No Misunderstanding BetweenThe Government And Other Communities Regulated In The Government Petrifiend The Head Of State ByRefreshing Public Service Article 86 Of Law Number 5 Of 1974 Which Was Formed By District CivilService Police Unit ,The Peak Of Which Failed On May 9 1992 Whose Members Consist Of A CombinationOf Members Of Public Order And Task Forces Managing Urban AreasKey Words : Behavior Of The Civil Service Police Init Order Service